A novel antidoping and medical care delivery model at the 2nd Summer Youth Olympic Games (2014), Nanjing China. Issue 13 (1st April 2015) - Mountjoy, Margo; Akef, Najla; Budgett, Richard; Greinig, Susan; Li, Guoping; Manikavasagam, Jegathesan; Soligard, Torbjorn; Haiming, Xai; Yang, Xiaoye
Abstract : Background: Antidoping and medical care delivery programmes are required at all large international multisport events. Objective: To document and critique the novel antidoping and medical care delivery models implemented at the 2nd Summer Youth Olympic Games, Nanjing 2014. Methods: The International Olympic Committee implemented two new models of delivery of antidoping and medical care at the YOG. A review of these models as well as the public health programme and two health educational initiatives in the Cultural and Educational Program was undertaken by the International Olympic Committee. Results: The implementation of the new antidoping model was feasible in the setting of the YOG. The antidoping rules and regulations of the International Olympic Committee were respected. This model enhanced the educational initiative and provided financial as well as human resource savings. The execution of the hospital-based venue model of medical care delivery at the YOG was also feasible in this setting. This model provided a practical infrastructure for the delivery of medical care at multisport events with the goal of providing optimum athlete healthcare. A public health prevention programme was implemented and no public health risks were encountered by the participants or the Nanjing citizens during the YOG. Finally, the implementation of the athlete health educational programmes within the Cultural and Educational Program provided athletes with an opportunity to improve their health and performance. Conclusions: To achieve the goal of protecting athlete health, and of employing effective doping control and education, new alternate models of antidoping and medical care delivery can be implemented.